(untitled) (AYUSHDHARA, 2022)
Sandhigatavāta is comparable to osteoarthritis of modern medicine. It is a kind of articular degenerative disorders that can affect any joints but generally observed weight bearing joints. It is prevalent since antiquity and commonly exists among elderly age group. Osteoarthritis is the second most common rheumatologic problem and it is the most frequent joint disease with a prevalence of 22% to 39% in India. It is predominant in females as compared to male. Variety of herbal and herbo-mineral formulations are mentioned in Ayurvedic lexicons for its management, Trayodaśāṇga guggulu is one of them. In this concern, we have laid down an emphasis in brief on Sandhigatavaāta and trying to explore the classical and contemporary pharmacological aspects of Trayodaśāṇga guggulu for its management.